Safety and tolerability of dienogest in endometriosis: pooled analysis from the European clinical study program - Strowitzki, Thomas; Faustmann, Thomas; Gerlinger, Christoph; Schumacher, Ulrike; Ahlers, Christiane; Seitz, Christian (International journal of women's health, 2015)
Safety and tolerability of dienogest in endometriosis: pooled analysis from the European clinical study program Thomas Strowitzki,1 Thomas Faustmann,2 Christoph Gerlinger,3,4 Ulrike Schumacher,5,6 Christiane Ahlers,7 Christian Seitz8 1Department of Gynecological Endocrinology and Reproductive Medicine, University of Heidelberg, Heidelberg, Germany; 2Bayer Pharma AG, Global Medical Affairs Women’s Healthcare, Berlin, Germany; 3Bayer Pharma AG, Global Research and Development Statistics, Berlin, Germany; 4Department of Gynecology, Obstetrics, and Reproductive Medicine, University Medical School of Saarland, Homburg/Saar, Germany; 5Jenapharm GmbH & Co KG, Medical Affairs Support, Jena, Germany; 6Center for Clinical Studies, Universitätsklinikum Jena, Jena, Germany; 7Bayer Pharma AG, Global Integrated Analysis and Lifecycle Management Statistics, Wuppertal, Germany; 8Bayer Pharma AG, Global Clinical Development Therapeutic Area Primary Care and Women’s Healthcare, Berlin, Germany Background: In four randomized, controlled, European trials, dienogest 2 mg once daily demonstrated significant efficacy for lesion reduction and reduction in pain intensity in endometriosis. We describe a pooled analysis of the safety and tolerability data from these trials to confirm and further characterize the safety profile of dienogest in the treatment of endometriosis.Methods: All 332 women treated with dienogest 2 mg who participated in the four clinical trials were included in the pooled analyses for safety assessments, including adverse events, laboratory tests, vital signs, body weight, and bleeding patterns. Safety variables were analyzed using descriptive statistics.Results: Pooled analyses of this large patient population confirmed that dienogest 2 mg is well tolerated, with a favorable safety profile extending over a period up to 65 weeks in women with endometriosis. The most common adverse drug reactions were headache, breast discomfort, depressed mood, and acne, each occurring in <10% of women. All these adverse events were generally of mild-to-moderate intensity and associated with low discontinuation rates. The bleeding pattern associated with dienogest 2 mg was well tolerated, and only two women (0.6%) reported bleeding events as the primary reason for premature discontinuation. Laboratory and vital sign assessments indicated no safety concerns for dienogest. Estradiol levels were maintained within the low-physiological range, in support of previous evidence indicating that dienogest 2 mg demonstrates therapeutic efficacy without inducing estradiol deficiency.Conclusion: In this pooled analysis of 332 women with endometriosis, dienogest was well tolerated with a favorable safety profile extending over a period of up to 65 weeks. There is a paucity of randomized trial evidence to support the use of many treatments in endometriosis. These pooled analyses from four clinical trials of dienogest 2 mg represent a contribution to evidence-based medicine in endometriosis, providing outcomes of potential relevance to daily practice. Keywords: progestins, endometriotic lesions, clinical trials, side effects, women
Gesehen am 22.06.2020